FAKTOR PENDUKUNG DAN PENGHAMBAT IMPLEMENTASI KEGIATAN AUDIT MATERNAL PERINATAL (AMP) DI KOTA SEMARANG (Study Kasus Pada Puskesmas Kedungmundu, Rumah Sakit Tugurejo dan Dinas Kesehatan Kota Semarang) - Ronald Mahudin; Sutopo Patria Jati; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2020)
Background: AMP activities in the city of Semarang have been running since 2011, but have not been optimal based on data on infant mortality cases conducted by AMP only around 20% -25% of the total number of cases.  This is not in line with the Republic of Indonesia Minister of Health Regulation No. 97 of 2014. So far the implementation of AMP in Semarang City has never been studied in depth to find out the supporting and inhibiting factors in its implementation.  This research is located in Kedungmundu Health Center, Tugurejo Hospital and Semarang City Health Office.Method: Qualitative research with a descriptive approach.  Data collection was done by indepth interview with purposive sampling.  The variables which are examined are the supporting and inhibiting factors of AMP activities.Results: the factors considered as supporting factors in the implementation of AMP activities were from the aspect of communication, namely on the dimensions of transmission (delivery of information), as well as clarity about information.  The second aspect is about resources, namely on budget resources and bureaucratic structural aspects, namely on the dimensions of fragmentation or division of tasks, while the inhibiting factor is on the communication aspect, namely on the dimension of consistency.  The aspect of resources from the dimension of human resources is also an inhibiting factor in the implementation of AMP activities in the city of Semarang, as well as aspects of the bureaucratic structure in the SOP dimension.